DAMPAK KEBIJAKAN MIGRASI TERHADAP DISTRIBUSI PENDAPATAN DI INDONESIA (Impact of Migration Policy on Income Distribution in Indonesia) - Yuni Sulistyorini; Rina Oktaviani; M. Parulian Hutagaol (Bina Ekonomi, 2014)
The Remittances of international migrants directly contribute in various ways to the welfare of their own household  and indirectly contribute to the economy as foreign exchange earnings for the country. Studies of the impact of migrant’s remittances on the distribution income in the receiving country report apparently conflicting result, some have found that remittance inflows increase the inequality of income and some have found that they decrease it. Therefore this study examines impact of remittance on income distribution in Indonesia. Analysis of Social Accounting Matrix (SAM) is used to determine impact of remittances on income distribution in Indonesia. Furthermore, analysis of income inequality using the Theil index is used to analyze the role of remittance receipts on income inequality. Grouping households in the SAM based on agricultural and non-agricultural sectors was conducted to determine which groups of households are most affected when there is a change receiving remittances from family members working abroad. The result obtained conclude that remittances contribute to increasing household incomes particularly the agricultural labor household. Furthermore, receipt of remittances from migrants decreased the inequality of income in Indonesia.